Early Childhood Gross Motor Development Through Sports Catching and Throwing Balls - Indri Ardia Putri; Latifatus Sa'adah; Moh Imam Mudi Al Ghofiqi (Civiliza Publishing, Indonesia., 2025)
This study aims to describe the development of gross motor skills in early childhood through ball-catching and throwing activities at TK Pertiwi Menden. Gross motor skills are an important aspect of child development because they are related to coordination, balance, muscle strength, and basic movement skills. The study uses a qualitative approach with a descriptive method through direct observation of children's activities. The results of the study show that ball-catching and throwing activities can improve hand-eye coordination, agility, balance, and large muscle strength. In addition, these activities also foster discipline, cooperation, and children's self-confidence.